An asymptotic method of consequent canonical substitutions of variables in the problem of translational-rotational motion of two rigid bodies. Part I - Saburova, N.Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2003)
An asymptotic method of consequent canonical substitutions of variables is considered for the problem of translational-rotational motion of two rigid bodies. A procedure for constructing the first approximation to the exact solution of the system of differential equations modeling the problem under consideration is developed.